THE ANXIETY OF RAJU RASTOGI IN RAJKUMAR HIRANI'S 3 IDIOTS MOVIE (2009): A PSYCHOANALYTIC APPROACH - KRISNAWATI, RINA (2011)
The object of the study is a movie 3 Idiots directed by Rajkumar Hirani. The study is to reveal how is anxiety reflected in 3 Idiots movie directed by Rajkumar Hirani published in 2009. The objective of the study is to analyze the structural elements in the movie and to analiyze the anxiety of the main characters using psychoanalytic. The researcher employs the descriptive qualitative research as a type of the research. The data sources divided into two, namely primary data source and secondary data source. The primary data source is the events of the movie and script of 3 Idiots and the secondary data source is biography of character. The method of collecting data are observation and library research. The technique of analyzing data is descriptive. Based on the analysis, the researcher draws two conclusions, first based on the structural analysis, Rajkumar Hirani wants to deliver moral message that education is not all about running blindly after success but its about aiming at excellence. From the structural analysis, it shows that each of the structural element are interrelated to each other. Second, based on the psychoanalytic analysis, Rajkumar Hirani reflects anxiety which is caused by the contradiction of his id, ego and superego.